The Effect of Love of Money And Tax Discrimination on Individual Taxpayers' Perceptions of Tax Evasion With Religiosity As A Moderating Variable - SORAYA, Chairunnisa Nur Azizah; Anggraini, Dahlia Tri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of love of money and tax discrimination on individual taxpayers' perceptions of tax evasion with religiosity as a moderating variable. The population of this study are taxpayers registered at KPP Pondok Aren. Based on purposive sampling, 100 respondents were used as samples in this study. This research is a quantitative research with survey method. This research data was processed using SmartPLS 4.1 software. The results showed that love of money and discrimination have a significant positive effect on tax evasion. Religiosity has a significant negative effect on tax evasion. Religiosity is not able to moderate the effect of Love of Money on Tax Evasion. Religiosity is not able to moderate the effect of Discrimination on Tax Evasion.